Relationship Between Vitamin D Level and Platelet Parameters in Children With Viral Respiratory Infections - Gavriela Feketea; Gavriela Feketea; Gavriela Feketea; Vasiliki Vlacha; Vasiliki Vlacha; Raluca Maria Pop; Ioana Corina Bocsan; Luminita Aurelia Stanciu; Anca Dana Buzoianu; Mihnea Zdrenghea; Mihnea Zdrenghea (Frontiers Media S.A., 2022)
Apart from their classical roles, both platelets and vitamin D play important roles in inflammation and infectious diseases. This study evaluated the platelet response to viral respiratory tract infection in children aged 4-16 years, 32 with influenza, 27 with non-influenza viral infection tested by nasopharyngeal swab and 21 healthy children of the same age. Blood count, including platelet count (PLT), mean platelet volume (MPV) and other platelet indices, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and vitamin D (vit D) levels were compared. The influenza group showed lower PLT and platelet mass (PLT*MPV), and the non-influenza group showed significantly lower MPV, which was correlated with the vit D levels, but not CRP or ESR, and the value vit D*MPV was significantly lower in this group. These results revealed that platelet activation in viral respiratory tract infections in children, as measured by MPV, is related to the vit D level, with differences between influenza and non-influenza infection.ConclusionsViral respiratory tract infection in children can diminish the platelet size most likely by suppressing the platelet activation. This response is associated with low levels of vit D. Whether the vit D status is associated with the virus-platelet immune/inflammatory process needs further investigation.